CREATING OF KNOWLEDGE DATABASE FOR ELECTRIC STORAGE OF INDUSTRY ENTERPRISES IN VINNYTSIA - Demov, O. D.; Shullie, Yu. A.; Zakharov, V. V. (Visnyk of Vinnytsia Politechnical Institute, 2014)
Creation of database of measures on the economy of electric power that any enterprise in Vinnytsya can apply, if the list of consumers is known, is considered in the article.